Moral Agency and the Paradox of Self-Interested Concern for the Future in Vasubandhu's Abhidharmakosabhāṣya - Hanner, Oren (Sophia, 2018)
It is a common view in modern scholarship on Buddhist ethics that attachment to the self constitutes a hindrance to ethics, whereas rejecting this type of attachment is a necessary condition for acting morally. The present article argues that in Vasubandhu's theory of agency, as formulated in the Abhidharmakosabhāṣya (Treasury of Metaphysics with Self-Commentary), a cognitive and psychological identification with a conventional, persisting self is a requisite for exercising moral agency. As such, this identification is essential for embracing the ethics of Buddhism and its way of life. The article delineates the method that Vasubandhu employs to account for the notion of a selfless moral agent, with particular emphasis on his strategies for dealing with one central aspect of agency, self-interested concern for the future.